Value of Brain Natriuretic Peptide in Predicting Prognosis of Coronary Artery Disease in Myocardial Infarction - Sadeghi, Roxana; Qobadighadikolaei, Roja; Ekhlaspour, Maryam; Sistanizad, Mohammad (Novelty in Biomedicine, 2020)
Background: Brain natriuretic peptide (BNP) is an important predictor of outcomes in patients with heart failure but the prognostic value of BNP elevation in patients with myocardial infarction (MI) is not completely defined. This study aims to identify the prognostic value of BNP in patients with MI. Materials and Methods: We studied patients with MI who were hospitalized in the Coronary Care Unit of Imam Hossein Hospital. Patients’ demographic data, past medical and drug history besides echocardiography report and BNP levels were documented during the hospital stay and echocardiography was repeated after 3 months. Results: This prospective observational cross-section study was done between January 2018 through January 2019. During the study period, 124 patients were recruited. There was significant negative correlation between BNP levels and ejection fraction (P=0.001), systolic blood pressure (P=0.012), diastolic blood pressure (P=0.003) and ratio between early mitral inflow velocity and early diastolic mitral annular velocity (E/e’) (P=0.03) and EF in follow up (P=0.001). The correlation between BNP levels with infarction location (P=0.40), arterial involvement in the left main coronary artery (P=0.15), left anterior descending artery (P=0.53), left circumflex artery (P= 0.97), right coronary artery (P=0.50) and hospital stay (P=0.66) were not significant. Conclusion: BNP is a valuable marker for predicting prognosis in patients with the acute coronary syndrome. Also, it could be considered as a prognostic long-term marker for predicting the EF of patients with AMI.